Tatakelola Utang dan Pembangunan Ekonomi Indonesia: Studi Komaparasi Antar Rezim Pemerintahan - Junaedi, Dedi; Arsyad, Muhammad Rizal (Ikatan Da'i Indonesia, 2022)
Research aims to analyze the effect of debt and differences in government regimes on economic growth. and poverty in Indonesia, (1940-2017). The study uses secondary data obtained from Bank Indonesia, National Development Planning Agency (Bappenas), the Central Statistics Agency (BPS), the World Bank, and other reference sources such as books, journals and scientific papers. The data used are the value of foreign debt, national income (GDP), population, number and ratio of the poor population, inflation rate in the period 1949 - 2021. The results of multiple regression analysis show: Foreign debt has a correlation with national economic conditions, especially the GDP and poverty. Debt tends to increase GDP and reduce poverty. In terms of debt a driver of the economy and poverty, the Soeharto Era and Habibie's Era tend to be different and better than the Soekarno Era. While Era Abdurrahman Wahid's debt management, Megawati Era, SBY Era and Jokowi's Era were no different or no better than Sukarno's Era. Although nationally can increase GDP and reduce poverty, debt cannot improve people's welfare. Foreign debt even tends to reduce the level of welfare of the people. This applies to all government regimes.